Low incidence of severe bacterial infections in hospitalised patients with COVID-19: A population-based registry study. Issue 2 (1st February 2023) - Ahava, M. J.; Kortela, E.; Forsblom, E.; Pätäri-Sampo, A.; Friberg, N.; Meretoja, A.; Kivivuori, S.-M.; Lappalainen, M.; Kurkela, S.; Järvinen, A.; Jarva, H.
Abstract: Background: Bacterial infections complicating COVID-19 are rare but present a challenging clinical entity. The aim of this study was to evaluate the incidence, aetiology and outcome of severe laboratory-verified bacterial infections in hospitalised patients with COVID-19. Methods: All laboratory-confirmed patients with COVID-19 admitted to specialised healthcare hospitals in the Capital Province of Finland during the first wave of COVID-19 between 27 February and 21 June 2020 were retrospectively studied. We gathered the blood and respiratory tract culture reports of these patients and analysed their association with 90-day case-fatality using multivariable regression analysis. Results: A severe bacterial infection was diagnosed in 40/585 (6.8%) patients with COVID-19. The range of bacteria was diverse, and the most common bacterial findings in respiratory samples were gram-negative, and in blood cultures gram-positive bacteria. Patients with severe bacterial infection had longer hospital stay (mean 31; SD 20 days) compared to patients without (mean 9; SD 9 days; p  < 0.001). Case-fatality was higher with bacterial infection (15% vs 11%), but the difference was not statistically significant (OR 1.38 CI95% 0.56–3.41). Conclusions: Severe bacterial infection complicating COVID-19 was a rare occurrence in our cohort. Our results are in line with the current understanding that antibiotic treatment for hospitalised COVID-19 patients should only be reserved for situations where a bacterial infection is strongly suspected. The ever-evolving landscape of the pandemic and recent advances in immunomodulatory treatment of COVID-19 patients underline the need for continuous vigilance concerning the possibility and frequency of nosocomial bacterial infections.